2016
DOI: 10.1210/en.2016-1444
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin Promotes Adipose Tissue Fitness and Insulin Sensitivity in Obese Males

Abstract: Excessive accumulation of body fat triggers insulin resistance and features of the metabolic syndrome. Recently, evidence has accumulated that obesity, type 2 diabetes, and metabolic syndrome are associated with reduced levels of serum prolactin (PRL) in humans and rodents, raising the question of whether low PRL levels contribute to metabolic dysfunction. Here, we have addressed this question by investigating the role of PRL in insulin sensitivity and adipose tissue fitness in obese rodents and humans. In die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
93
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(100 citation statements)
references
References 67 publications
6
93
0
1
Order By: Relevance
“…The effects of milk PRL in the offspring's adipose tissue are supported by our findings showing that oral PRL treatment to the neonatal offspring from HFD-fed mothers results in reduced VAT adiposity and increased subcutaneous adipocyte hyperplasia. In agreement, we have shown that in adult obese rats, PRL treatment promotes adipocyte hyperplasia while reducing visceral adipocyte hypertrophy (23).…”
Section: Discussionsupporting
confidence: 83%
“…The effects of milk PRL in the offspring's adipose tissue are supported by our findings showing that oral PRL treatment to the neonatal offspring from HFD-fed mothers results in reduced VAT adiposity and increased subcutaneous adipocyte hyperplasia. In agreement, we have shown that in adult obese rats, PRL treatment promotes adipocyte hyperplasia while reducing visceral adipocyte hypertrophy (23).…”
Section: Discussionsupporting
confidence: 83%
“…In fact, several recent prospective studies suggested that the associations between prolactin and risk of type 2 diabetes and the metabolic syndrome were more likely to be beneficial in women but tended to be null or even detrimental in men [1721]. The reason underlying this sex difference is unclear, as both beneficial and detrimental effects of prolactin on IR have been reported in men [12, 44]. Nevertheless, our data, coupled with prior evidence, suggest that prolactin may be related to pathogenic pathways leading to the development of type 2 diabetes in women.…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin is a principal determinant of prenatal/postnatal development of pancreatic islet cells, as well as islet adaptation during pregnancy [5, 14, 20, 53]. It is also involved in the regulation of hepatic/adipocytic insulin sensitivity [12, 13], and can indirectly affect hypothalamic dopamine release and energy/glucose homeostasis [54]. In our study, prolactin was inversely correlated with C-peptide and adjusting for C-peptide attenuated the association between prolactin and type 2 diabetes (particularly for bioactive prolactin).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, obese patients treated with bromocriptine or those with T2DM that did not show a substantial increase in prolactin levels, surprisingly still demonstrated an improvement in glucose control [49]. While remaining within the normal range, increased levels of prolactin have been suggested by several studies to reduce insulin resistance and the occurrence of T2DM [53][54][55]. In their study, Li et al attempted to evaluate whether healthy women with high prolactin levels were more protected from T2DM when compared to those with lower circulating prolactin.…”
Section: Managementmentioning
confidence: 99%